Identification of construction solutions using thermography - Ferreira, Ana Vaz (2020)
In the context of building rehabilitation, the phase of inspection and diagnosis is essential to identify the materials and techniques applied, thus seeking intervention strategies compatible with the existing building. The use of infrared cameras for this phase of diagnostic may contribute to a less intrusive survey, without the need to use tests that damage the element. The work performed consisted of a survey of study cases representing the utilization of different techniques and materials. With the objective of identifying the constructive solutions and applied materials, the active thermography was used, using the sun as a source of heating of the element, and Thermograms were acquired during the cooling process of the elements. The thermograms were visually analyzed in order to interpret the temperature variation and radiation emission by the elements. The work allowed to assess the use of singular constructive solutions, namely the ' Cruz de Santo André ' or ' Taipa de Fasquio ', as well as current construction solutions with the use of masonry of stone or brick and structure in concrete.